2017
DOI: 10.1021/jacs.7b05164
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[6]uril-Promoted Click Chemistry for Protein Modification

Abstract: Azide-alkyne cycloaddition is a powerful reaction for the formation of bioconjugates. When catalyzed by Cu(I) or strain promotion, this cycloaddition is considered to be a "click" reaction with many applications in chemical biology and materials science. We report a new type of azide-alkyne click chemistry for the synthesis of protein conjugates using cucurbit[6]uril (CB6) supramolecular chemistry. CB6-promoted azide-alkyne cycloaddition has been previously used for the synthesis of rotaxanes but has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…[35,116] Since the seminal work by Mock and coworkers in 1989 describing [3 + 2] alkyne-azide cycloadditions catalyzed with CB [6] [117] and subsequent applications, [77,118,119] a large number of studies have shown the potential of the CB[n] family members to promote reactions within their cavity or at their portal, and a majority of those propose solid rationales for the observed rate changes. [120] Recent and thorough reviews by Scherman [101] and Nau, [23] as well as ours a few years earlier [100] cover CB[n]-promoted reactions in detail. [120] Recent and thorough reviews by Scherman [101] and Nau, [23] as well as ours a few years earlier [100] cover CB[n]-promoted reactions in detail.…”
Section: Guest Release and Capture Controlled By Ancillary Reactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…[35,116] Since the seminal work by Mock and coworkers in 1989 describing [3 + 2] alkyne-azide cycloadditions catalyzed with CB [6] [117] and subsequent applications, [77,118,119] a large number of studies have shown the potential of the CB[n] family members to promote reactions within their cavity or at their portal, and a majority of those propose solid rationales for the observed rate changes. [120] Recent and thorough reviews by Scherman [101] and Nau, [23] as well as ours a few years earlier [100] cover CB[n]-promoted reactions in detail. [120] Recent and thorough reviews by Scherman [101] and Nau, [23] as well as ours a few years earlier [100] cover CB[n]-promoted reactions in detail.…”
Section: Guest Release and Capture Controlled By Ancillary Reactionsmentioning
confidence: 95%
“…We take the advantage here to highlight the remarkable and very recent functionalization of proteins by Francis and coworkers, who managed to prepare protein À DNA, protein À peptide, protein À polymer, and protein À drug conjugates using the CB[6]-catalyzed alkyne-azide cycloaddition. [120] Recent and thorough reviews by Scherman [101] and Nau, [23] as well as ours a few years earlier [100] cover CB[n]-promoted reactions in detail. Those include (1) CB [7]-catalyzed [4 + 4] photodimerizations [121] (2) [2 + 2] cycloadditions of stilbene derivatives, [122][123][124] coumarins [125] and styryl dyes [126] inside CB [8], (3) [4 + 4] cycloadditions of anthracene derivatives inside CB [8]; [127][128][129] (4) the photodimerization of 2naphthalene-carbonitriles [130] and naphthoates; [131] (5) the photoreaction of diazabicylo[2.2.2]alk-2-enes inside CB [7], whose outcomes is strongly influenced by metal cations interacting 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 with the rim of the macrocycle;…”
Section: Impact Of Cucurbiturils On Reaction Ratesmentioning
confidence: 95%
“…The TMV-rotaxane conjugate (final concentration of 1 µM) was suspended in the supernatant solution and the H2O2 mediated cleavage reaction was monitored by 129 Xe HyperCEST over several hours. Untreated cells (TNF−) remained in the 'turn-off' state even after 8 h, while a stable 'turn-on' response was observed for TNF+ cells after 2 h and lasted until 24 h. This rotaxane-based approach could monitor the low micromolar H2O2 levels in cells using 129 Xe HyperCEST NMR [191,192].…”
Section: Molecular Rotaxanesmentioning
confidence: 99%
“…It has served as ideal support or as a capping agent for metal nanoparticles . The catalytic activity of CB[6] has been explored elegantly in alkyne‐azide cycloaddition reactions (Click chemistry) for modifications of proteins . Immobilized palladium nanoparticles (CB[6]‐Pd) have been reported as efficient heterogeneous catalysts for Suzuki and Heck reactions, aerobic oxidation of alcohol, and hydrogenation reactions .…”
Section: Introductionmentioning
confidence: 99%